Innovative design and development practices in aerospace and automotive engineering : I-DAD, February 22-24, 2016 - Bajpai, Ram P.; Chandrasekhar, U. (Springer, 2016)
The book presents the best articles presented by researchers, academicians and industrial experts in the International Conference on "Innovative Design and Development Practices in Aerospace and Automotive Engineering (I-DAD 2016)". The book discusses new concept designs, analysis and manufacturing technologies, where more swing is for improved performance through specific and/or multifunctional linguistic design aspects to downsize the system, improve weight to strength ratio, fuel efficiency, better operational capability at room and elevated temperatures, reduced wear and tear, NVH aspects while balancing the challenges of beyond Euro IV/Barat Stage IV emission norms, Greenhouse effects and recyclable materials. The innovative methods discussed in the book will serve as a reference material for educational and research organizations, as well as industry, to take up challenging projects of mutual interest.
Includes author index.
Keywords: Engineering design -- Congresses.; Aerospace engineering -- Congresses.; Motor vehicles -- Design and construction -- Congresses.; elektronické knihy; electronic books